Prevalence of malocclusion in public school students in the mixed dentition phase and its association with early loss of deciduous teeth - Marianella Aguilar Ventura FADEL; Bianca Zimmermann SANTOS; Raquel Pippi ANTONIAZZI; Leonardo KOERICH; Vera Lúcia BOSCO; Arno LOCKS (Dental Press Editora, 2022)
ABSTRACT Objective: To determine the prevalence of malocclusion and its association with the early loss of deciduous teeth and other factors in children in the mixed dentition phase, aged six to eight years, enrolled in public schools in southern Brazil. Methods: A cross-sectional study was conducted with a representative sample of 528 children from municipal public schools in 2009. Data collection involved a clinical examination for the determination of early tooth loss, dental caries, tongue pressure and malocclusion (outcome), as well as the administration of a questionnaire. Poisson regression analysis with robust variance was used to model the association between malocclusion and the independent variables. Results: The prevalence of malocclusion and early tooth loss was 69.1% and 21.8%, respectively. In the raw data analysis, malocclusion was associated with age, early tooth loss, dental caries and tongue pressure. After the adjustment, the likelihood of malocclusion was greater among children older than eight years, those who exerted tongue pressure on the teeth and those with early tooth loss. The likelihood of malocclusion was 24% greater among children with early tooth loss, compared to those without tooth loss. Conclusion: The early loss of deciduous teeth was associated with the occurrence of malocclusion in the children studied.